On Restriction Optimal Fixpoints - Margaryan, Vahan K. (Mathematical Problems of Computer Science, 2021)
Optimal ¯xpoints extract maximum consistent information from recursive programs. However, optimal ¯xpoints, although they always exist for a recursive operator, aren't necessarily computable. We have introduced a modi¯ed notion of the optimal ¯xpoint, where the recursive operators are restricted to computable inputs. Existence results for and properties of this ¯xpoint are summarized in the article.